After some much apreciated help on here by several people i would like to display this question complete with working out and soloution, could people please pick up on any mistakes i may have made

Many Thanks

Question 2

2x + y = -1

x + 2y = 4

Multiply the first equation by 2

Thus gives 4x + 2y = -2

Multiply the second equation by 4

Thus gives 4x + 8y = 16

Now subtract equation 2 from equation 1

Thus 0 + -6y = -18

Thus y = 3

Enter the value for y back into the first equation which gives…

2x + 3 = -1

Thus x must equal -2

The solutions are..

Y= 3

X= -2